1980
DOI: 10.1080/03014223.1980.10423795
|View full text |Cite
|
Sign up to set email alerts
|

Arhopalus ferus(Coleoptera: Cerambycidae): structure and function of the female reproductive system

Abstract: Arhopalus terus (Mulsant) female pupae and adults were dissected, and both internal and external genitalia are described. The external genitalia involve segments 8 and 9. Segment 9 and its appendag·es are modified into a long ovipositor whlich telescopes with segment 8 into segment 7 when retracted. The internal genitalia include ovaries, bursa copulatrix, spermatheca, spermathecal gland, vagina, and accessory glands. The terminology applied to coleopteran genital anatomy is critically discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…Therefore, the evolution of female proctiger membranization is probably driven by natural selection favouring these functions, a process that is independent of males. This idea is consistent with the hypothesis that gains of flexibility in insect ovipositors may be advantageous to lay eggs in softer and deeper substrates (Hubweber & Schmitt, 2010;Hutcheson, 1980) or inside niche sites previously prepared with the mouthparts, as in many weevils (Marvaldi, Sequeira, O'Brien, & Farrel, 2002). Another line of evidence for the role of natural selection in driving the evolution of female proctigers is the fact that the traits studied are broadly Since natural selection is the prime driver of ovipositor evolution (Muto et al, 2018;Roff & Mousseau, 1999) and males obviously lack the function, it is clear that alternative sources of selection have acted on male proctigers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the evolution of female proctiger membranization is probably driven by natural selection favouring these functions, a process that is independent of males. This idea is consistent with the hypothesis that gains of flexibility in insect ovipositors may be advantageous to lay eggs in softer and deeper substrates (Hubweber & Schmitt, 2010;Hutcheson, 1980) or inside niche sites previously prepared with the mouthparts, as in many weevils (Marvaldi, Sequeira, O'Brien, & Farrel, 2002). Another line of evidence for the role of natural selection in driving the evolution of female proctigers is the fact that the traits studied are broadly Since natural selection is the prime driver of ovipositor evolution (Muto et al, 2018;Roff & Mousseau, 1999) and males obviously lack the function, it is clear that alternative sources of selection have acted on male proctigers.…”
Section: Discussionsupporting
confidence: 88%
“…Regardless of whether different processes may have acted on the trait in distinct lineages, the fact that males and females show strong evolutionary association still indicates that baculi changes are adaptive. It has been suggested that the evolution of different types of baculi or paired rods in the ovipositor, not only restricted to the proctiger but also in other parts like the paraprocts and gonocoxites (Lawrence et al., 2011), provide the ovipositor with longitudinal strength and rigidity (Hutcheson, 1980; Tanner, 1927). Thus, baculi may appear as a result of a trade‐off between flexibility and mechanical integrity, counterbalancing possible downsides of excessive membranization in soft ovipositors in some species.…”
Section: Discussionmentioning
confidence: 99%
“…Females emerge sexually mature and they mate almost immediately. Once they mate, females disperse while males generally remain in the emergence site (Hutcheson 1980). Something similar seems to occur in A. rusticus.…”
Section: Discussionmentioning
confidence: 62%
“…En el pico del periodo de actividad de los adultos, el número de machos superó al de hembras. Esto se debe a que los machos emergen unos días antes para fecundar a las hembras recién emergidas, observación que coincide con lo registrado para A. ferus y A. rusticus (Hosking & Bain, 1977;Hutcheson, 1980;Pedemonte, 2014). Esto explica también que las hembras sin pareja dejaron descendencia porque fueron fecundadas dentro de las jaulas entomológicas antes de ser llevadas al laboratorio.…”
Section: áRboles Trampaunclassified